The Using Jigsaw Learning Strategy to Increase Students’ Speaking Ability at The Language Boarding House of Salafiyah-Syafi’iyah Islamic School: English - Septiana Wandira; Dwi Nur Hadiyansah Siswoyo; rafika Zayyanah (JOEY: Journal of English Ibrahimy, 2024)
To find out whether the Jigsaw Learning Strategy can increase students’ speaking ability. It was necessary to carry out the jigsaw learning strategy because there was a phenomenon where students often felt uninterested and bored following the speaking learning activity.This research used a classroom action research (CAR) that was designed in 2 cycles. Each cycle are consisting of planning, implementation, observation, and reflection. The subject was students of the Elementary B class of the Language Boarding House of Salafiyah-Syafi’iyah, Situbondo, which consisted of 17 students. It produced a negative impact to the students’ speaking ability. Based on the speaking test that was produced in the pre-cycle only 9 students among 17 who reached the complete score with the criteria of minimum completeness was 75 and the completeness percentage was 52,94% included the criteria of very low. In cycle 1, 13 students among 17 students reached the complete score with the completeness percentage was 76,47%, it got increase and included to the criteria of average. For the cycle 2, 16 among 17 students achieved the complete score with the completeness percentage was 94,11%. It got very effective increase and included to the criteria of very high.